Effect of Discontinuing Sodium Bicarbonate on Fermentation Process of Palm Oil Mill Effluent - Irvan; Trisakti, B.; Sosanty, F.; Tomiuchi, Y. (Asian Journal of Chemistry, 2015)
The aim of this research is to investigate the effect of discontinuing sodium bicarbonate on the fermentation of palm oil mill effluent to biogas. This research was conducted in a two liters continuous stirred tank reactor at thermophilic temperature of 55 °C. Fresh palm oil mill effluent from Adolina mill without further treatment was used as feed. The result showed that at hydraulic retention time of 6 days and discontinuing of sodium bicarbonate addition, there was no significant effect on the production of biogas, change of pH, volatile solid and total solid degradation, except alkalinity. By discontinuing sodium bicarbonate, biogas production was in the range of 4-6 L/day, while by adding sodium bicarbonate was 6-10 L/day. About 45 % of volatile solid degradation by discontinuing of sodium bicarbonate addition was obtained during the digestion, while by using sodium bicarbonate was 55 %. pH of digester was relatively stable with average value was 6.7 and alkalinity was 2000 mg/L.